Status Gizi Mahasiswa Universitas Pertahanan Republik Indonesia Program S1 Angkatan 1: Nutritional Status of Indonesia Defense University’s Student S1 Program Batch 1 - Dwi Monik Purnamasari; Yolanda Safitri; Elies Fitriani; Rachma Hidana; Adristi Anargya Athallah; Roy Envito Utama; Cahya Wahyudi Januarta; Astikahilda Maria Pangemanan; Handrian Rahman Purawijaya; Grace Joselini Corlesa; Alfa Januar Krista (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2021)
Indonesia is currently having a double burden of malnutrition (undernutrition and obesity). Nutritional status affects human health quality. In 2020, Indonesia Defense University launched a new undergraduate program to fulfill the needs of human resources in military and ministry of defense. Early detection of nutritional status is needed to determine so that malnutrition can be followed up. This research was conducted by using a cross sectional method with the 288 subjects. Measurement of nutritional status was done through examination of Body Mass Index (BMI) and body fat percentage by using a Bioelectrical impedance analysis (BIA). Result showed that based on BMI, 8% of all subjects were obese, 64.6% were in normal nutritional status, 20.1% were overweight, and 7.3% were undernourished. If classified by gender, 6.7% of male students were obese, 24.7% were overweight, 7.3% were underweight, and 61.2% were in normal nutritional status, while for female cadets, 10% were obese, 70% were normal, 12.7% were overweight, and 7.3% were underweight. Based on the percentage of body fat by using the BIA, it was found that 83.3% of subjects were normal and 16.7% of all subjects were obese. If classified by gender, 2.2% of male students and 40% of female students were obese. It can be concluded that the prevalence of obesity and underweight among all cadets according to BMI were relatively low, but the proportion of overweight and percent body fat among cadets were quite high.